1996
DOI: 10.2190/an6l-6qbq-76g0-0n9a
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Caregivers of Patients with Alzheimer's Disease: A Review and Analysis of Content, Process, and Outcomes

Abstract: Current reviews of the caregiver intervention literature have focused primarily on the outcomes of interventions for caregivers and general methodological limitations of individual studies (i.e., sampling and recruitment issues, adequacy of outcome measures, and generalization issues). Little attention has been paid to the specific factors affecting the therapeutic process, including the intensity and integrity of the interventions used. The purpose of this review is to examine closely the content and process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
0
7

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(161 citation statements)
references
References 96 publications
5
149
0
7
Order By: Relevance
“…This study builds upon the few existing CG intervention studies that address the need for CG health promotion and improved physical health outcomes. 6 Furthermore, this study is unique in that we have included a multicultural population of CGs; and also builds upon the recommendations for tailoring interventions to meet age-specific needs of the target population. 57 We have shown that lifestyle physical activity can be applied to CGs of persons with AD and that the EPA intervention can lead to measurable increases in physical activity in at least half of these CGs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study builds upon the few existing CG intervention studies that address the need for CG health promotion and improved physical health outcomes. 6 Furthermore, this study is unique in that we have included a multicultural population of CGs; and also builds upon the recommendations for tailoring interventions to meet age-specific needs of the target population. 57 We have shown that lifestyle physical activity can be applied to CGs of persons with AD and that the EPA intervention can lead to measurable increases in physical activity in at least half of these CGs.…”
Section: Resultsmentioning
confidence: 99%
“…Few interventions have addressed the need for CG health promotion and improved physical health outcomes. 6 Effective interventions are needed to help CGs maintain optimal mental and physical health as they assume their familial and social roles with less risk to their own well-being. 7,8 Recent literature suggests that increasing lifestyle physical activity is one of the most effective health promotion strategies with benefits to both mental and physical health and decreased mortality.…”
mentioning
confidence: 99%
“…Despite the strong theoretical framework, a theoretical framework for social support interventions is hardly ever presented in the empirical research literature (Bourgeois et al 1996;Turner & Shepherd, 1999;Helgeson & Gottlieb, 2000). The evidence on social support interventions on weight management summarized in Table 1 generally shows positive outcomes of social support interventions.…”
Section: Implications: Social Support In Future Research and Intervenmentioning
confidence: 99%
“…Care giving implies a continuous confrontation with problematic, unpredictable situations. Coping strategies describe the way caregivers handle these situations (7,12,21,28). Caregivers can acquire more efficient coping strategies spontaneously or through training by professionals.…”
Section: Discussionmentioning
confidence: 99%
“…These caregivers tend to report a significantly higher prevalence of depression and workload than caregivers of chronically ill relatives and non-caregivers (4,8,10,18,25,27). Prematurely ending home care by institutionalizing the demented relative is one major consequence of caregiver burnout (2,5,7,20,29,33).…”
Section: Introductionmentioning
confidence: 99%